Preparing Mental Health Professionals to Work With Survivors of Intimate Partner Violence: A Comprehensive Systematic Review of the Literature. Issue 3 (August 2021) - Sutton, Amber; Beech, Haley; Ozturk, Burcu; Nelson-Gardell, Debra
Intimate partner violence (IPV) affects millions of individuals across all demographics and ethnicities. Research has revealed a direct link between experiencing IPV and having adverse physical, mental, and financial outcomes which can create difficulties for survivors. Survivors experiencing these adverse outcomes are likely to seek out support to address these issues, increasing the likelihood that they will encounter mental health professionals (MHPs). MHPs can play a significant role in assessing and addressing IPV since they are often critical access points for those experiencing violence and are likely to counsel victims. Accurate identification of current or past IPV victimization is crucial to avoiding the potential of misdiagnosis of survivors. In addition, by applying and emphasizing an understanding of the connection between individual and structural explorations of gender, race, class, and other socially constructed identities, mental health professionals can utilize the skills necessary to challenge inequalities, which in turn can encourage survivors to create strategies that make sense to themselves and their communities. This study explores what is known about how MHPs are prepared to work with IPV. Peer-reviewed journals that were published between 2005 and 2019 were reviewed systematically to develop a better understanding of the existing literature. We sought to answer the question, "What is known about how MHPs are prepared to work with IPV?" This review identified 20 articles regarding training experiences of MHPs and how these experiences shaped their responses to and practice with those experiencing IPV.